A Convenient Protocol for the Synthesis of Fatty Acid Amides - Johansson, Silje J. R.; Johannessen, Tonje; Ellefsen, Christiane F.; Ristun, Mali S.; Antonsen, Simen; Hansen, Trond V.; Stenstrøm, Yngve; Nolsøe, Jens M. J. (Synlett, 2019)
Several classes of biologically occurring fatty acid amides have been reported from mammalian and plant sources. Many amides conjugated with fatty acids of mammalian origin exhibit specific activation of individual receptors. Their potential as pharmacological tools or as lead compounds towards the development of novel therapeutics is of great interest. Hence, access to such amides by a practical, high-yielding and scalable protocol without affecting the geometry or position of sensitive functionalities is needed. A protocol that meets all these requirements involves activation of the corresponding acid with carbonyl diimidazole (CDI) followed by reaction with the desired amine or its hydrochloride. More than fifty compounds have been prepared in generally high yields.
Keywords: fatty acid amides; CDI; AM404; ethanolamide; N-acylethanolamines (NAEs); N-acyl dopamines (NAPs); N-acyl amino acids (NAAs); anandamide